An evidence‐based practice guideline of the National Society of Genetic Counselors for telehealth genetic counseling. Issue 1 (30th August 2022) - Green, Sarah; Hartzfeld, Deborah; Terry, Alissa Bovee; Fissell, Kristi; Friedman, Sue; Paolino, Nicholas; Principe, Kate; Sandbach, John; Trzupek, Karmen; Winheld, Stephanie; Malinowski, Jennifer
Abstract: There are currently no practice guidelines available for genetic counseling using telehealth modalities. This evidence‐based practice guideline was developed in response to increasing use of alternative service delivery models for genetic counseling, specifically telephone and video‐based genetic counseling (telehealth genetic counseling or THGC). A recent systematic evidence review (SER) compared outcomes of THGC with in‐person genetic counseling and found that for the majority of studied outcomes, THGC was a non‐inferior and comparable service delivery model. The SER results were used to develop this guideline. The current and anticipated future use of THGC, including the influence of the COVID‐19 pandemic, provides the context for this guideline. Recommendation: The Telehealth Practice Guideline author workgroup conditionally recommends telehealth genetic counseling, either via telephone or video, as a delivery method for genetic counseling. Depending on factors unique to individual healthcare systems and provider and patient populations, THGC may be the only service delivery model available or may be utilized in addition to other service delivery models including in‐person genetic counseling. The evidence shows large desirable effects, minor undesirable effects, and increased equity for patients when THGC is available. THGC may reduce or remove existing barriers to patient access to genetic counseling, such as medical conditions and/or disabilities that may affect a patient's ability to travel, inflexible work or school schedules, and lack of reliable transportation, finances, or dependent care. THGC is likely acceptable to key groups impacted by its use and is feasible to implement. Certain patient populations may require additional resources or encounter more barriers in using telemedicine services in general. For these populations, THGC can still be a valuable option if solutions are available.